(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Antimicrobial resistance (AMR) poses a significant threat to global public health, rendering once-effective antibiotics increasingly ineffective and leading to higher rates of morbidity, mortality, and healthcare costs. Addressing AMR requires collaborative efforts at local, national, and international levels. This article explores the urgent need for global action to combat AMR, highlighting the interconnectedness of antimicrobial resistance and the importance of coordinated responses. Key challenges in combatting AMR, including limited development of new antibiotics and disparities in access to effective antimicrobial stewardship programs, are discussed. The role of collaborative initiatives, such as the Global Antimicrobial Resistance Surveillance System (GLASS) and the Antimicrobial Resistance (AMR) Action Fund, is emphasized, along with key strategies for collaboration, including enhancing antimicrobial stewardship, investing in research and development, improving surveillance and data sharing, and engaging with agricultural and veterinary sectors. The article concludes with a call to action for governments, policymakers, healthcare professionals, and the public to prioritize antimicrobial stewardship and work together to preserve the effectiveness of antimicrobial drugs for future generations.